Molecular mechanisms of dendrite morphogenesis - Arikkath, Jyothi (Frontiers in Cellular Neuroscience, 2012)
Dendrites are key integrators of synaptic information in neurons and play vital roles in neuronal plasticity. Hence, it is necessary that dendrite arborization is precisely controlled and coordinated with synaptic activity to ensure appropriate functional neural network integrity. In the past several years, it has become increasingly clear that several cell intrinsic and extrinsic mechanisms contribute to dendritic arborization. In this review, we will discuss some of the molecular mechanisms that regulate dendrite morphogenesis, particularly in cortical and hippocampal pyramidal neurons and some of the implications of aberrant dendritic morphology for human disease. Finally, we will discuss the current challenges and future directions in the field.